Sechs neue Hispinen aus Südamerika (Coleoptera: Chrysomelidae). 181. Beitrag zur Kenntnis der Hispinae. - Uhmann, Erich Leo Ludwig (Contributions to Entomology = Beiträge zur Entomologie, 1957)
The author describes 6 Hispinae from different territories of South America. Five of them are figured. Three species are dedicated to scientists still working, one species is named after a German botanist at the time esteemed for his collecting. Nomenclatural Acts bucki Uhmann, 1957 (Cephaloleia), spec. n. wallisi Uhmann, 1957 (Homalispa), spec. n. sorathae Uhmann, 1957 (Octhispa), spec. n. bimaculata Uhmann, 1957 (Odontispa), spec. n. kaestneri Uhmann, 1957 (Sceloenopla), spec. n. sachtlebeni Uhmann, 1957 (Sceloenopla Oncosispa), spec. n.